Vở bài tập tiếng Việt 5 /. T.1 Nguyễn Minh Thuyết chủ biên, Hoàng Hòa Bình, Trần Mạnh Hưởng, Trần Thị Hiền Lương, Nguyễn Trí Nguyễn Minh Thuyết chủ biên, Hoàng Hòa Bình, Trần Mạnh Hưởng, Trần Thị Hiền Lương, Nguyễn Trí / Nguyễn Minh Thuyết chủ biên, Hoàng Hòa Bình, Trần Mạnh Hưởng, Trần Thị Hiền Lương, Nguyễn Trí - Nguyễn, Minh Thuyết chủ biên
Đầu trang nhan đề:Vở bài tập tiếng Việt 5